Faktor Penyebab Perubahan Morfologi Desa Ngadas, Poncokusumo, Kabupaten Malang - Santoso, Dian Kartika; Wikantiyoso, Respati (Local Wisdom Jurnal Ilmiah Kajian Kearifan Lokal, 2018)
Ngadas Village has been designated as Tourism Village. Such determination may affect the morphology of Ngadas Village. Although tourism activities are regarded as things that can cause changes in the morphology of the region but do not rule out the possibility of other factors. Thus, it is very important to know the factors other causes. Thus, massive morphological changes can be controlled by knowing the causal factors. Consequently, the sustainability of Ngadas as a traditional tourism village can be maintained. The method used in this research is the descriptive qualitative method through synchronic and diachronic approach. In addition, this research also used spatial analysis to know morphologyâ€™s development of Ngadas Village through Google Earth image in 2004, 2012, and 2017. The result of the research indicates that factors causing a morphological change of Ngadas Village are the cultural factor, natural factor, demographic factors, tourism development factor, building and land allotment, and government policy.Â DOI: https://doi.org/10.26905/lw.v10i2.2678